Analysis of Flood Discharge at Catchment Area of West Jurang Mangu Reservoir using HEC-HMS - Purnaditya, Ngakan Putu; Jannah, Dahlia Raudothul; Subekti, Subekti; Priyambodho, Bambang Adhi; Wigati, Restu (JURUSAN TEKNIK SIPIL, 2025)
High rainfall in Indonesia is one of the causes of flooding, especially in vulnerable areas such as watersheds. In addition to high rainfall, an increase in population and land use that is not in accordance with its function can worsen watershed conditions and cause an increase in flood risk. South Tangerang City is one of the areas prone to flooding, so flood control efforts are carried out such as widening rivers, raising embankments, and building retention ponds. Around the catchment area of the West Jurang Mangu Reservoir, flooding with a height of 50 60 cm still occurs, so further research was carried out at that location. In this study, the research method used QGIS to determine the catchment area, followed by hydrological analysis of the planned flood discharge using the HSS Synder method and modeling with HEC-HMS software. The results showed that the planned flood discharge using HSS Synder at return periods of 2, 5, 10, 25, and 50 years was 2.55 m3/s; 3.599 m3/s; 4.261 m3/s; 5.033 m3/s; and 5.718 m3/s.